The GA4GH Variation Representation Specification: A computational framework for variation representation and federated identification - Alex H. Wagner; Lawrence Babb; Gil Alterovitz; Michael Baudis; Matthew Brush; Daniel L. Cameron; Melissa Cline; Malachi Griffith; Obi L. Griffith; Sarah E. Hunt; David Kreda; Jennifer M. Lee; et al. (Elsevier, 2021)
Summary: Maximizing the personal, public, research, and clinical value of genomic information will require the reliable exchange of genetic variation data. We report here the Variation Representation Specification (VRS, pronounced "verse"), an extensible framework for the computable representation of variation that complements contemporary human-readable and flat file standards for genomic variation representation. VRS provides semantically precise representations of variation and leverages this design to enable federated identification of biomolecular variation with globally consistent and unique computed identifiers. The VRS framework includes a terminology and information model, machine-readable schema, data sharing conventions, and a reference implementation, each of which is intended to be broadly useful and freely available for community use. VRS was developed by a partnership among national information resource providers, public initiatives, and diagnostic testing laboratories under the auspices of the Global Alliance for Genomics and Health (GA4GH).